The Effectiveness of Text-Based Strategy to Teach Adjectives and Adverbs: An Experimental Study on the Second Semester Students of the English Department at the Faculty of Language and Culture UNTAG Semarang - Soedhono, R. Kumbino Ari (FEB UNTAG Semarang, 2012)
A foundational part of what the writer does as a teacher of English as a foreign language involves grammar. When the writer examines students’ ability of grammar, the writer certainly expects that they are able to apply grammar correctly in sentences as well as in texts. Unfortunately, this does not always happen. Hence, in this research the writer will discuss one of the teaching strategies to teach grammar (especially adjectives and adverbs), that is text-based teaching strategy. The purpose of this research is to measure the ability of the second semester students in the use of adjectives and adverbs as a basis of legitimate fact for the need of a new teaching strategy, and how effective is the text-based strategy to teach adjectives and adverbs to the second semester students of the English Department at the Faculty of Language and Culture Untag Semarang. The research design is a quasi-experimental study. The data of how high is the ability of the students in using adjectives and adverbs is taken by using pre-test and post-test. Meanwhile, the data of how effective is the text-based strategy to teach adjectives and adverbs to the students is tested by using the average difference of the post-test of the experimental and the control group. The result of how high the ability of students in using adjectives and adverbs in sentences and texts was from the pre-test result and from the post-test result and it can be seen that the post-test result is better than the pre-test result and it means that H0 is rejected and H1 is accepted. Based on the testing of the average difference (using t-test), it was found that tobtained > ttable. Hence, H0 is rejected and H1 is accepted. This means that teaching adjectives and adverbs using text-based strategy is effective in this institution.